High-order singularities of 5R planar parallel robots - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
Singularity analysis of parallel manipulators is an active research field in robotics. The present article derives for the first time in the literature a condition under which a five-bar parallel robot encounters high-order parallel singularities. In this regard, by focusing on the planar 5R mechanism, a theorem is given in terms of the slope of its coupler curve at the parallel singular configurations. At high-order parallel singularities, the associated determinant vanishes simultaneously with at least its first-order time derivative. The determination of such singularities is quite important since in their presence, some special conditions should be satisfied for bounded inverse dynamic solutions.
Keywords: Parallel manipulators; Planar 5R mechanism; Robot dynamics; Singularity; Singularity order; INVERSE DYNAMICS; MOTION CONTROL; FREE ZONES; MANIPULATORS; MECHANISMS; WORKSPACE; MACHINE; DESIGN; ACTUATION; KINEMATICS